Analisis Tingkat Kepuasan Nasabah Terhadap Kualitas Pelayanan Pada Bank BRI Cabang Kahu - Ismaniar, A.; Asriati, Asriati; Indriana, Indriana (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to analyze the level of customer satisfaction regarding the quality of services provided by the BRI Bank Kahu Branch. High-quality banking services are essential for building customer loyalty and enhancing the institution's image amid increasingly competitive banking industry conditions. The research method employed is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The findings indicate that most customers are satisfied with the services received, particularly in terms of staff friendliness, service speed, and ease of access. However, several issues remain, such as long queues during peak hours and insufficient service promotion to communities outside the Palattae area. Strategies implemented by the BRI Kahu Branch to improve customer satisfaction include enhancing staff competence through training, increasing the number of tellers during busy periods, and utilizing digital services such as mobile banking. The study concludes that service quality significantly influences customer satisfaction, and continuous improvement is necessary to meet the evolving needs and expectations of customers.